Comparison of performance of two large-scale vertical-flow constructed wetlands treating wastewater treatment plant tail-water: Contaminants removal and associated microbial community. (15th January 2021) - Zhu, Tongdou; Gao, Jingqing; Huang, Zhenzhen; Shang, Na; Gao, Jianlei; Zhang, Jinliang; Cai, Ming
Abstract: The removal efficiency of contaminants in large-scale integrated vertical-flow constructed wetland (IVCW) and vertical-flow constructed wetland (VCW) for wastewater treatment plant (WWTP) tail-water was evaluated, and the microbial community was also investigated in this study. The results for 14 months study period indicated that 40.05% chemical oxygen demand (COD), 45.47% ammonia nitrogen (NH4 + -N), 62.55% total phosphorus (TP), 55.53% total nitrogen (TN) and 57.20% total suspended solids (TSS) average removal efficiencies were achieved in the IVCW. There was a poor performance of TN removal in the VCW, with an average removal efficiency of 38.13%. There was no significant seasonal difference in TP removal, and a strong positive correlation between influent TP load and removed load. The high-throughput sequencing analysis revealed that Proteobacteria, Planctomycetes, Bacteroidetes and Acidobacteria were dominant in nature and wetland systems. The relative abundance of nitrifying bacteria, denitrifying bacteria and anammox bacteria confirmed that nitrification, denitrification and anammox may be the main processes for nitrogen removal in the IVCW. Highlights: The removal of COD, NH4 + -N and TN had obvious seasonal changes, except for TP. The better capacity of nutrients removal was achieved in IVCW. Nitrification, denitrification and anammox may be the main processes for N removal. IVCW would be an economical and applicable technology for the upgrading of WTTPs.